Enhanced Microwave Absorption Performance in Sr-Modified La2NiO4±δ Nickelate With High Dielectric Loss - Liu, Sheng; Cheng, Yulan; He, Jun; Yan, Shuoqing; Luo, Heng; Deng, Lianwen (Frontiers in Materials, 2020)
This work aims to achieve the excellent microwave absorption in layered dielectric nickelate compounds. The phase, microstructure, electromagnetic properties, and microwave absorption of the Sr-modified La2–xSrxNiO4±δ (x = 0, 0.3, 0.5, 0.75) nickelates were investigated, determining and analyzing the role of Sr doping level. All compounds reveal the single tetragonal phase identified as the I4/mmm space group, and the lattice parameters correlate with the doping content, evidenced by Rietveld refinement. By introducing strontium, the pronouncedly increased electronic conductivity contributes to the high dielectric loss, which gives rise to a superior attenuation ability and absorbing bandwidth. A minimum reflection loss of -21.07 dB was found in La2–xSrxNiO4±δ (x = 0.75) at a thickness of 1.9 mm, covering the effective bandwidth of 2.9 GHz. This enhanced microwave absorbing performance in nickelate shows promise in the radar absorbing field.